1991
DOI: 10.1111/j.1741-6248.1991.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Family Businesses Really Different? European Experiences from STRATOS

Abstract: Using observations of 1,132 small‐ and medium‐sized enterprises in eight European countries, a comparison is made of family and nonfamily businesses. The variables compared concern values and attitudes, objectives, and strategic behavior. The data reveal that family businesses are inwardly directed or closed family‐related systems. Among their managers are fewer pioneers than “all‐rounders” and organizers; as a consequence, their strategic behavior is rather conservative. Therefore, family businesses should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
250
2
11

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(275 citation statements)
references
References 6 publications
12
250
2
11
Order By: Relevance
“…An exception is the work of De Mel and colleagues (2009) which use a range of various indicators to provide evidence that the success of informal businesses in Sri Lanka is determined by not only the skills but also the acumen of entrepreneurs. Such findings reinforce the evidence that the role of the entrepreneur is more evident in small enterprises in every strategic aspect, including innovation activities (Donckels and Fröhlich, 1991).…”
Section: Informality Innovation and Firms' Growthsupporting
confidence: 87%
“…An exception is the work of De Mel and colleagues (2009) which use a range of various indicators to provide evidence that the success of informal businesses in Sri Lanka is determined by not only the skills but also the acumen of entrepreneurs. Such findings reinforce the evidence that the role of the entrepreneur is more evident in small enterprises in every strategic aspect, including innovation activities (Donckels and Fröhlich, 1991).…”
Section: Informality Innovation and Firms' Growthsupporting
confidence: 87%
“…On the other hand, family business research has shown that family firms differ in their values and attitudes, objectives, and strategic behavior from nonfamily firms (e.g. Donckels and Fröhlich 1991). This leads us to hypothesize that organizational and managerial innovations have a different level of importance in family firms when compared to non-family firms.…”
Section: Development Of Hypothesesmentioning
confidence: 96%
“…Earlier studies generally show that family firms are less likely to internationalise than non-family firms owing to weak information and control systems, inward orientation, difficulties or reluctance in hiring external managerial talent, and fear of the loss of power and control (Donckels and Fröhlich, 1991;Gallo and Sveen, 1991;Gallo and Pont, 1996;Harris, Martinez and Ward, 1994). Recent studies show similar results (Cerrato and Piva, 2012;Fernández and Nieto, 2005;Graves and Thomas, 2003, 2006, 2008.…”
Section: Theoretical Overviewmentioning
confidence: 90%